Cluster of influenza A cases in vaccinated population of adults in Virology Laboratory in Glasgow in December 2012. Issue 2 (May 2014) - Bradley-Stewart, A; Miller, RS; MacLean, A; Aitken, C; Whittaker, L; Gregory, V; Daniels, R; Gunson, R
Background and aims: The majority of influenza infections during the 2012/2013 influenza season in Scotland have been due to influenza A H3N2. We report an outbreak of influenza A H3N2 in a vaccinated population of adults in the Regional Virology Laboratory in Glasgow. This investigation was carried out to confirm the epidemiological link between cases. Methods and results: Staff with clinical symptoms of influenza-like illness were included. Samples were tested by real-time polymerase chain reaction and sequencing. Staff were interviewed to obtain information regarding symptom onset and vaccination status. Eight confirmed cases and six clinically diagnosed cases were reported, which all occurred within 4 days of a lunchtime Christmas quiz. The eight samples subtyped as H3 virus. The haemagglutinin gene in the confirmed cases was sequenced and shown to be identical. Most of the attendees had been immunised against influenza with the same vaccine batch at least 6 weeks earlier. Conclusion: This outbreak appears to have been an isolated incident, which arose due to a social event that provided the ideal conditions for transmission of a respiratory disease. It may have been compounded by low-vaccine effectiveness this season. Sequence data supported the epidemiological link.